European integration and political conflict - Marks, Gary 1952-; Steenbergen, Marco R. 1963- (Cambridge University Press, 2004)
Over the past half-century, Europe has experienced the most radical reallocation of authority that has ever taken place in peace-time, yet the ideological conflicts that will emerge from this are only now becoming apparent. The editors of this 2004 volume, Gary Marks and Marco Steenbergen, have brought together a formidable group of scholars of European and comparative politics to investigate patterns of conflict that are arising in the European Union. Using diverse sources of data, and examining a range of actors, including citizens, political parties, members of the European Parliament, social movements, and interest groups, the authors of this volume conclude that political contestation concerning European integration is indeed rooted in the basic conflicts that have shaped political life in Western Europe for many years. This comprehensive volume provides an analysis of political conflict in the European Union
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Europäische Union; European Union; Politik; Pressure groups / European Union countries; Lobbying / European Union countries; Political participation / European Union countries; Political parties / European Union countries; Politische Auseinandersetzung; Mitgliedsstaaten; Politische Beteiligung; Partei; Europäische Integration; Politischer Konflikt; Europäische Union. Mitgliedsstaaten; European Union countries / Politics and government; Konferenzschrift -- 1998 -- Chapel Hill NC; Aufsatzsammlung